Strategic selection and design of the first auction item: analyzing auction dynamics through “Motion in Mind” and “Potential Reinforcement Energy” - Li, Siqi; Mohd Nor Akmal Khalid; Iida, Hiroyuki (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study examines how the strategic selection and design of the first auction item using the "Motion in Mind" and "Potential Reinforcement Energy" frameworks influence auction dynamics, affecting participation and competitiveness. The initial item's selection, based on its starting and expected prices, triggers bidder motivations such as personal expression, artistic appreciation, and status signaling, driven by gameplay incentives, which dictate the auction's competitive pace. Data from major auction houses, including Christie's and Sotheby's, were analyzed using correlation analysis and multivariate regression modeling. The findings indicate that the strategic placement of the initial item significantly impacts auction velocity and the deviation of final auction prices from pre-auction estimates, highlighting the auction's multidimensional nature influenced by economic, psychological, and social factors. The research suggests that effective auction design requires accommodating diverse bidder preferences across financial, personal, and social dimensions. A deep understanding of bidder motivations, precise pricing strategies, and nuanced market analysis is crucial for maintaining participant engagement and optimizing auction success. This paper underscores the transcendence of auctions beyond economic transactions, involving a complex interplay of strategic, self-actualization, and engagement motives, as well as non-economic utilities, reflecting broader human behavior and social interactions.